ELABORATION OF THE MODEL OF INNOVATIVE MANAGEMENT OF EDUCATIONAL PROCESS INTENDED FOR ADAPTATION TO THE CHANGES IN THE EXTERNAL INSTITUTIONAL ENVIRONMENT - L. V. Vorontsova; T. V. Kramin (Russian Journal of Economics and Law, 2012)
The work discusses the requirements to the modern educational process and its features. The authors propose and ground the additional set of competences necessary for the students to ensure their competitiveness in the modern labour market. The contours of the innovative educational management model are constructed, which are intended for adaptation to the changing institutional environment. The authors show the transactional essence of the expenditures of the model implementation, and present the grouping of these expenditures.